Exploring Π-conjugated carbon nanomaterials for biomedical applications - Prasad, Kenath Priyanka (2016)
Nanomaterials are at the forefront of the rapidly changing landscape in nano medicine and nanobiotechnology. Their unique size and surface-dependent properties (e.g. physicochemical, optical etc) make nanomaterials engineered from π-conjugated carbons such as semiconducting polymers and graphene suitable for a variety of biomedical applications. At present, the research on π-conjugated nanocarbons is in its infancy and thus, many challenges and opportunities exist for the generation of customized nanomaterials for biomedical applications. This thesis work aims to develop π-conjugated carbon-based nanomaterials with tailored properties for applications in cellular imaging, therapy and biodevices. Firstly, an electropolymerization based facile strategy was conceived to synthesize polymer quantum dots from one-dimensional semiconducting polymers. Using this strategy polymer dots with small sizes, high brightness, tunable photoluminescence, excellent photostability and superb biocompatibility were derived from two non-fluorescent semiconducting polymers poly(3,4-ethylenedioxythiophene) (PEDOT) and poly(2,2’-bithiophene). The small sized, fluorescent PEDOT-Pdots showed good quantum yields (~13%) and were utilized as bioimaging probes and optical sensors for toxic mercury ions with good detection limits. Subsequently, the developed synthesis route was modified and used to tailor polymer dots with improved brightness and small sizes. The synthesized pTh-Pdots demonstrated unique solvatochromism behaviour and were utilized to label and differentiate early endosomes and lysosomes to track the endocytic pathway. In addition to lighting up biological pathways, identifying new antibacterial alternatives is increasingly becoming more urgent. The aqueous suspensions of the amphiphilic pTh-Pdots were found to be potent synthetic antibacterial alternatives, thereby demonstrating for the first time a new area of application for the versatile polymer dots. Finally, the synergistic effect between two π-conjugated carbon allotropes was used to enhance the performance of a bio-power device. Enzymatic biofuel based cells can be considered as alternative power generation biodevices with a long-term goal as bio-renewable power sources for implantable medical devices. 1D single walled carbon nanotubes (SWCNT) were composited with freestanding graphene (a three-dimensional architecture of 2D graphene) to fabricate bioelectrodes for a glucose/oxygen powered enzymatic biofuel cell (EBFC). The 3D graphene-SWCNT-enzyme based bio-electrodes fabricated from two conjugated carbon allotropes (graphene and carbon nanotubes) exhibited one of the highest performances till date. With its extensive electrochemically active surface areas, high enzyme loading, efficient, and superb electron transfer, the EBFC performance approached open circuit voltages of 1.2 V and power densities of 2.27 ± 0.11 mW cm-2.